Trainee Teachers’ Learning Style with Ict: a Survey Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A person's learning style (LS) is the initial focus, processing, and retention of novel and challenging knowledge through individual differences in these perceptual channels. Personal styles are what make each person unique from the rest of the crowd. The term "Learning Style" is often understood to relate to an individual's set of preconceived notions, personal preferences, and deliberate actions that serve to facilitate learning. This research was conducted to learn how different groups of student teachers approach information and communication technology for learning, and to identify any noteworthy differences. Gender, Marital Status, and Technical Proficiency). 500 pre-service teachers from B.Ed. programmes in Paschim and Purba Medinipur participated in the research. The sample was picked using a method called Simple Random Sampling. The t test and descriptive statistics were used to examine the data. According to the results of the research, male and female student instructors have quite different approaches to learning using information and communication technologies. Student instructors who are married or single do not have substantially different ICT learning styles. There is little distinction in the approaches to ICT education used by student teachers who are computer proficient and those who are not.